Comparative Transcriptomics in Ebola Makona-Infected Ferrets, Nonhuman Primates, and Humans. (23rd August 2018) - Cross, Robert W; Speranza, Emily; Borisevich, Viktoriya; Widen, Steven G; Wood, Thomas G; Shim, Rebecca S; Adams, Ricky D; Gerhardt, Dawn M; Bennett, Richard S; Honko, Anna N; Johnson, Joshua C; Hensley, Lisa E; et al.
Abstract: The domestic ferret is a uniformly lethal model of infection for 3 species of Ebolavirus known to be pathogenic in humans. Reagents to systematically analyze the ferret host response to infection are lacking; however, the recent publication of a draft ferret genome has opened the potential for transcriptional analysis of ferret models of disease. In this work, we present comparative analysis of longitudinally sampled blood taken from ferrets and nonhuman primates infected with lethal doses of the Makona variant of Zaire ebolavirus . Strong induction of proinflammatory and prothrombotic signaling programs were present in both ferrets and nonhuman primates, and both transcriptomes were similar to previously published datasets of fatal cases of human Ebola virus infection.